The Effectiveness of Problem-Based Instruction in Peer Teaching Activities for Islamic Cultural History (SKI) at MAN Insan Cendekia - Riadi, Buya; Afgani, Muhammad Win; Marlina, Leny; Febriyanti, Febriyanti (The Future of Education Journal, 2025)
This research focuses on how the application of the Problem Based Instruction learning model is a learning model based on the interaction between stimulus and response, which in this case is learning and the environment of MAN IC OKI which is one example of a madrasa that implements a boarding school system, where students are required to live or live in dormitories with fairly strict rules. The purpose of this study was to determine the effectiveness of the problem-based instruction learning model in peer teaching activities in Islamic Cultural History subjects in class IX MAN IC OKI. As for achieving these objectives, descriptive quantitative research methods are used by using comparisons between pretest scores and posttest scores after treatment. Data taken using interview techniques and comparison between pretest and posttest scores. The sample was taken as many as 11 students from 117 class XI students at MAN Insan Cendekia OKI. Based on this research, the results obtained that the problem-based instruction learning model is effectively applied in peer teaching activities in the subject of Islamic Cultural History to students of class XI MAN IC OKI Gazal Semester 2024-2025, it can also be seen from the increasing value and enthusiasm for learning of the sample students.